UNRAVELING THE AMBIGUITY BETWEEN COGNITION AND DEPRESSION: A LONGITUDINAL ANALYSIS OF OLDER ADULTS. (20th December 2022) - Roessler, Meghann; Manchella, Mohit; Singh, Anmoldeep; Coleman, Max; Francis, Heather; Saykin, Andrew; Risacher, Shannon; Apostolova, Liana
Abstract: Research on directionality of the relationship between cognitive functioning and depression is ambiguous, especially when considering implications for patients with mild cognitive impairment or Alzheimer disease (AD). Previous research suggests that depression in late life could be a pre-clinical manifestation of AD before other cognitive symptoms are detectable. Some research supports the hypothesis that level of depression can independently predict level of cognition. Other research suggests that depression is a risk factor for developing dementia or AD late in life. Further research on the impact of subjective cognitive decline versus objective cognitive performance in association with depressive symptoms is a critical area to explore. Using data from the Social Networks in Alzheimer Disease (SNAD) study and the Indiana Alzheimer Disease Research Center (IADRC), we conducted a preliminary longitudinal analysis of 196 focal subjects (Mage = 71.6 years, Pfemale = 63%). Interviews conducted one year apart were leveraged to elucidate the bidirectional relationship between depressive symptomology and cognition. Using a lagged dependent variable approach controlling for age, sex, race, and education, the results indicate that only executive function predicts depression at timepoint 2 (-0.31 SD, p< 0.001). However, depression predicts focal Cognitive Change Index (CCI) (0.06 SD, p< 0.05), processing speed (-0.04 SD, p< 0.05), and episodic memory (-0.04 SD, p< 0.05). Other cognitive domains examined, including attention, language, visual/spatial skills, MoCA score, and informant-rated CCI, were not significant as predictors or as outcomes. These results suggest that depression may be a more robust predictor of cognition than cognition is of depression.